Effect of Nb addition on the microstructure and mechanical properties of additively manufactured Ti alloys - Yeo, Kai Ni (Nanyang Technological University, 2021)
In an ageing population today, there is an increasing demand for biomedical implants to replace hard tissue failures in most elderly. Currently, titanium alloys are one of the most popular biomaterials used in the manufacture of implants due to its high corrosion resistance and high strength. Amongst which, Ti-6Al-4V alloy is most commonly used. However, many literatures pointed that Ti-6Al-4V alloys may no longer be suitable, primarily due to the presence of cyto- toxicity elements (V) and its high modulus of elasticity which result in stress shielding effect. Therefore, there is a need to seek for alternatives. In this work, the effect of addition of Niobium (Nb) into Titanium alloys was studied. This study focused on the changes in microstructure and mechanical properties of the alloys. Ti-42Nb and Ti-45Nb were selected to represent the Ti-Nb alloys. Microscopically, Ti-Nb alloys were found to have majority body-centred cubic crystallographic structures, indicating that they were beta phase alloys. Moreover, they had near equiaxed beta grains with random orientation. Mechanically, Ti-Nb alloys demonstrated lower hardness, yield strength and ultimate tensile strength as compared to Ti-6Al-4V. However, these came with attractive trade- offs as the Ti-Nb were discovered to possess significantly lower modulus of elasticity and higher ductility. Hence, this paper concludes that the Ti-Nb alloys have the potential to replace the Ti-6Al-4V as biomaterial for implants.